Celecoxib-Loaded Electrospun Fibrous Antiadhesion Membranes Reduce COX-2/PGE2 Induced Inflammation and Epidural Fibrosis in a Rat Failed Back Surgery Syndrome Model - Wei Wang; Yunhao Wang; Tengfei Lou; Mingqian Ding; Juehong Li; Hao Xiong; Zhixiao Yao; Yingying Ma; Huajiang Chen; Shenghe Liu (Neural Plasticity)
To date, failed back surgery syndrome (FBSS) remains a therapy-refractory clinical condition after spinal surgery. The antiadhesion membrane is applied to prevent FBSS by isolating fibrosis; however, the inflammation stimulated by the foreign body and surgical trauma needs to be further resolved simultaneously. Therefore, we developed new electrospun polycaprolactone (PCL) fibrous membranes loaded with celecoxib (CEL) to prevent fibrosis and inflammation associated with FBSS. The CEL-loaded PCL fibers were randomly distributed, and the drug was released over two weeks. Fluorescence micrographs revealed that the fibroblasts proliferated less on the PCL-CEL fibrous membranes than in the PCL group and the blank control. In the rat laminectomy model after 4 weeks, magnetic resonance imaging of epidural fibrosis was least in the PCL-CEL group. Expression of COX-2 and PGE2 was lower in the PCL-CEL group. It concluded that the CEL-loaded PCL membrane could reduce fibrosis and inflammation in a rat model of FBSS via COX-2/PGE2 signaling pathways.